PERILAKU KEAGAMAAN ORANG TUA DALAM MENGEMBANGKAN KARAKTER REMAJA DI KELURAHAN KENALI ASAM ATAS KECAMATAN KOTA BARU JAMBI - Maharani, Ria (Jurnal Al-Ashlah, 2017)
This research is located in Kenali Asam Atas, which is motivated by religious behavior problems Parents in Developing Character of Adolescent in Kenali Asam Atas, which is not optimal. This study answer the question why religious behavior of Parents in Developing Character of Adolescent in Kenali Asam Atas is not optimal?These results indicate that the behavior of Religion Parents in Developing Character of Adolescent in Kenali Asam Atas is not optimal because the religious behavior of parents in Kenali Asam Atas in this regard can not say better, because the parents them selves had not been able to give example to their adolescent a good behavior. The teenage characters in the Kenali Asam Atas Jambi tend toward negative due to weak communication and attention that given to neighborhood Association and also parents and the community in developing the adolescent characters toward the better, as well as the lack of attention of parents to religious behavior which is owned by their adolescent. Religious behavior Parents in improving adolescent characters in the Kenali Asam Atas Jambi exemplifies this by way of a good religious behavior in adolescent, parents also always advised adolescent to never leave prayer five times, some parents also put their children to institute Islamic religious education as MTS or MA, and parents also send adolescent to participate in religious activities in mosques or in their environment Recognize in Kenali Asam Atas.Â Keywords: Religious Behavior, Parents, Adolescent Character